Written in Blood: Blood Devotion in Gianfrancesco Pico’s Staurostichon - Piana, Marco (Renaissance and Reformation / Renaissance et Réforme, 2019)
This article aims to provide an analysis of Gianfrancesco Pico della Mirandola’s hymn Staurostichon in view of other examples of Savonarolan blood devotion. Staurostichon describes a supernatural event that took place in Germany between 1501 and 1503, when unusual rainfalls started to mark people’s bodies and garments with shapes of red crosses and other symbols generally connected to Christ’s Passion. Often interpreted as a rain of divine blood, the Kreuzwunder gave free rein to the imagination of many historians, astrologers, and prophets of the time. Deeply engrained with Savonarola’s devotion to Christ’s blood and wounds, Gianfrancesco Pico’s Staurostichon seeks to provide a biblical and prophetic explanation of the event: an explanation that is soaked in the gory events of the sacred Scriptures and the lives of the saints.